ASSESSMENT OF AWARENESS LEVEL OF OWN DISEASE IN PATIENTS WITH STABLE ARTERIAL HYPERTENSION - G. F. Andreeva; V. M. Gorbunov; S. Y. Martsevich (Рациональная фармакотерапия в кардиологии)
Arterial hypertension (AH) is the most frequent risk factor of cardiovascular diseases and related mortality in all developed countries. Altough therapy with antihypertensive drugs significantly reduces this risk, patients with stable mild hypertension have poor compliance with the treatment. The reasons and levels of inadequacy of antihypertensive therapy in this group of patients are well-known.Aim. To evaluate the awareness level of own disease, adequacy of therapy only in those patients with stable mild arterial hypertension, who are complied with recommendations of physicians concerning AH treatment and changing of mode of life. It was also planned to reveal possible grounds for inadequate secondary prevention of cardiovascular disease.Materials and methods. 76 patiens with stable mild arterial hypertension were included into study. They didn’t have any serious concomitant diseases and were complied with the recommendations of physicians concerning secondary prevention of cardiovascular disease. Questionnaire of State Research Center for Preventive Medicine “Assessment of awareness level of own disease in patients with stable arterial hypertension” was used in the study.Results. It was revealed, that the majority of patients, invoved in the study, were nonsmokers and regularly took antihypertensive drugs. 70% of questioned patients reached the target arterial blood pressure levels, while patients with arterial hypertension in general Russia population received regular and efficient treatment in less than 30-20%. Drugs treatment of questioned patients almost didn’t differ from that, which received patients in out-patient clinics of Moscow: in both cases ACE inhibitors were preferred. Only 29% of questioned patients knew their lipid levels in blood and none of the patients took drugs, reducing levels of lipids in blood. Half of the patients, that took part in our study, had increased level of body mass index.Conclusions. Inadequate secondary prevention of cardiovascular disease in patients, complied with the recommendations of physicians is mainly connected with 1) insufficient awareness of physicians of new drugs and treatment schemes; 2) underevaluation of hyperlipidemia as one of the main risk factors of cardiovascular disease and related mortality by physicians, and consequent absence of hypolipidic therapy; 3) negligence to such risk factor as exceeding weight and consequent unawareness of body mass index norms by patients with arterial hypertension.